1999
DOI: 10.1038/sj.gt.3300951
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to green fluorescent protein: implications for gene therapy

Abstract: Green fluorescent protein (GFP) is a widely used intracellu-EGFP did lead to rapid development of disease in immunolar reporter molecule to assess gene transfer and deficient Nu/Nu mice. Mice surviving BM185/EGFP leukeexpression. A potential use for GFP is as a co-expressed mia challenge developed high cytotoxic T lymphocyte marker, to select and enrich gene-modified cells by flow (CTL) responses against EGFP-expressing cells. Furthercytometry. Processed peptides derived from GFP and more, immune stimulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
248
2
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(260 citation statements)
references
References 33 publications
6
248
2
4
Order By: Relevance
“…These data are all the more impressive considering the suggestion from previous work that the GFP protein itself is immunogenic. 26 When GFP-positive SCs were transplanted into SCID mice, 100% of the grafts survived as determined by both fluorescence microscopy and immunohistochemistry for GATA-4 (a marker for SCs). In contrast, the survival of GFP SCs in Balb/c mice was more variable with surviving SCs detected in 50-70% of the allografts.…”
Section: Discussionmentioning
confidence: 99%
“…These data are all the more impressive considering the suggestion from previous work that the GFP protein itself is immunogenic. 26 When GFP-positive SCs were transplanted into SCID mice, 100% of the grafts survived as determined by both fluorescence microscopy and immunohistochemistry for GATA-4 (a marker for SCs). In contrast, the survival of GFP SCs in Balb/c mice was more variable with surviving SCs detected in 50-70% of the allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that eGFP is immunogenic in human, 26 non-human primates 27,28 and in murine models. 29,30 Evidences also suggest immune rejection of transplanted eGFP-positive cells in non-human primate recipients in myeloablative 27 as well as nonablative settings. 28 Hence, using eGFP as a model antigen, herein we show that Lenti-eGFP-transduced DC could effectively process and present the eGFP-derived antigenic peptides to contaminating lymphocytes in DC culture and reproducibly generate CTLs capable of eliminating the eGFP-expressing DCs.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that GFP is an immunogen for C57BL/6 and BALB/c mice in tumor studies (Gambotto et al, 2000;Stripecke et al, 2001). In contrast, others have failed to reproduce these findings (Denaro et al, 2001).…”
Section: Discussionmentioning
confidence: 99%